Predicted Impact of Aeration on Toxicity From Trihalomethanes and Other Disinfection Byproducts. Issue 10 (1st October 2017) - Huang, Yifeng; Zhang, Hong; Zamyadi, Arash; Andrews, Susan; Hofmann, Ron
Abstract : The removal by aeration of a mixture of disinfection byproducts (DBPs) was modeled, and the resulting impact on overall cytotoxicity or genotoxicity was calculated. Both the aeration model and the toxicity model were simplistic, but all assumptions were made to err on the side of overestimating DBP volatility to try to demonstrate a possible health benefit. The results predicted that aeration designed to remove 90% of chloroform would leave the concentrations of many other DBPs largely unaffected; since these other DBPs are predicted to contribute to the majority of the cytotoxicity and genotoxicity, the models used in the current research predicted only a 4% reduction in both cytotoxicity and genotoxicity. Although this study was a preliminary screening limited by simplistic models, it underscores a need to conduct more research in this area.